Impact of whole body electromyostimulation on cardiometabolic risk factors in older women with sarcopenic obesity: the randomized controlled FORMOsA-sarcopenic obesity study - Wittmann K; Sieber C; von Stengel S; Kohl M; Freiberger E; Jakob F; Lell M; Engelke K; Kemmler W (Clinical Interventions in Aging, 2016)
Katharina Wittmann,1 Cornel Sieber,2 Simon von Stengel,1 Matthias Kohl,3 Ellen Freiberger,2 Franz Jakob,4 Michael Lell,5 Klaus Engelke,1 Wolfgang Kemmler1 1Institute of Medical Physics, Faculty of Medicine, Friedrich-Alexander University of Erlangen-Nürnberg, 2Institute for Biomedicine of Aging, Faculty of Medicine, Friedrich-Alexander University of Erlangen-Nürnberg, Erlangen, 3Faculty of Medical and Life Sciences, University of Furtwangen, 4Musculoskeletal Research Center, University of Würzburg, Würzburg, 5Department of Radiology and Nuclear Medicine, Klinikum Nürnberg, Paracelsus Medizinische Privatuniversität, Nürnberg, Germany Background: Sarcopenic obesity (SO) is characterized by a combination of low muscle and high fat mass with an additive negative effect of both conditions on cardiometabolic risk. The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on the metabolic syndrome (MetS) in community-dwelling women aged ≥70 years with SO. Methods: The study was conducted in an ambulatory university setting. Seventy-five community-dwelling women aged ≥70 years with SO living in Northern Bavaria, Germany, were randomly allocated to either 6 months of WB-EMS application with (WB-EMS&P) or without (WB-EMS) dietary supplementation (150 kcal/day, 56% protein) or a non-training control group (CG). WB-EMS included one session of 20 min (85 Hz, 350 µs, 4 s of strain–4 s of rest) per week with moderate-to-high intensity. The primary study endpoint was the MetS Z-score with the components waist circumference (WC), mean arterial pressure (MAP), triglycerides, fasting plasma glucose, and high-density lipoprotein cholesterol (HDL-C); secondary study endpoints were changes in these determining variables. Results: MetS Z-score decreased in both groups; however, changes compared with the CG were significant (P=0.001) in the WB-EMS&P group only. On analyzing the components of the MetS, significant positive effects for both WB-EMS groups (P≤0.038) were identified for MAP, while the WB-EMS group significantly differed for WC (P=0.036), and the WB-EMS&P group significantly differed for HDL-C (P=0.006) from the CG. No significant differences were observed between the WB-EMS groups. Conclusion: The study clearly confirms the favorable effect of WB-EMS application on the MetS in community-dwelling women aged ≥70 years with SO. However, protein-enriched supplements did not increase effects of WB-EMS alone. In summary, we considered this novel technology an effective and safe method to prevent cardiometabolic risk factors and diseases in older women unable or unwilling to exercise conventionally. Keywords: sarcopenia, obesity, whole-body electromyostimulation, cardiovascular, metabolic risk, metabolic syndrome, community-dwelling, older people